Use of Oenological Tannins to Protect the Colour of Rosé Wine in a Bioprotection Strategy with Metschnikowia pulcherrima - Maëlys Puyo; Scott Simonin; Géraldine Klein; Vanessa David-Vaizant; Natalia Quijada-Morín; Hervé Alexandre; Raphaëlle Tourdot-Maréchal (Foods, 2023)
Although bioprotection is now recognised as an alternative to SO2 for limiting microbial spoilage, it does not guarantee protection against oxidation. This limits its application, more specifically for rosé winemaking. Oenological tannins present antioxidant properties, which could represent an interesting alternative to SO2 to protect must and wines against oxidation. A combination of the inoculation of a bioprotectant yeast strain and the addition of oenological tannins was tested to eliminate sulfites during the pre-fermentative step of rosé winemaking. In this experiment carried out in a winery, two oenological tannins were compared: quebracho and gall nut tannins. The antioxidant efficiency of tannins was compared to that of SO2. Colorimetric assays associated with chemical analyses of anthocyanins and phenolic compounds confirmed that the use of bioprotection alone did not protect the wine from oxidation. An addition of oenological tannins on musts stabilized the colour of bioprotected rosé wine in a similar way that SO2 addition did. Quebracho tannins appeared more efficient than gall nut tannins. The colour differences observed cannot be explained either by the concentration or forms of anthocyanins. However, the addition of tannins led to better protection of oxidation-sensitive phenolic compounds comparable to that obtained with the addition of sulfites.